Financial Management System (QRIS) based on UTAUT Model Approach in Jabodetabek - A Kadim; Nardi Sunardi (International Journal of Artificial Intelligence Research, 2022)
The focus of this research is the use of e-money information technology by adapting the UTAUT model to determine the effect of performance expectations, business expectations, social influences and facilitation conditions to public interest in using Server Base Payment System: Quick Response Code Indonesian Standard (QRIS) in Jabodetabek. This study uses a quantitative descriptive method. The population of this study was Jakarta, Bogor, Depok, Tangerang, Bekasi (Jabodetabek) citizen and the sample of fespondent are 125 by using targeted sampling method. Data analysis by lisrel. The results of this study informed that behavioral intersest was not affect with positive and significant by performance expectations and social influence but was affect with positive and signifianct by effort expectation. Jabodetabek citizens usage behavior in QRIS payment tools was affect with positive and significant by facilities conditions and behavioral interest.